2018
DOI: 10.1186/s12874-018-0501-2
|View full text |Cite
|
Sign up to set email alerts
|

Validating the use of veterans affairs tobacco health factors for assessing change in smoking status: accuracy, availability, and approach

Abstract: BackgroundAccurate smoking status is key for research purposes, but can be costly and difficult to measure. Within the Veteran’s Health Administration (VA), smoking status is recorded as part of routine care as “health factors” (HF)—fields that researchers can query through the electronic health record (EHR). Many researchers are interested in using these fields to track changes in smoking status over time, however the validity of this measure for assessing change is unknown. The primary goal of this project w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 18 publications
(15 reference statements)
0
16
0
Order By: Relevance
“…Our primary outcome was tobacco cessation ("quit") during the post-period, coded as a binary yes/ no variable. Using methods similar to prior EHR-based studies, 11,[19][20][21][22] a person was identified as "quit" if the last recorded tobacco-use status during the pre-period indicated that the patient was a current user, and if there was at least one subsequent measurement documented in the postperiod that indicated the patient's status was a "nonuser" (eg, former user, not a current user). We extracted the following tobacco cessation medications from EHR medication orders: bupropion, varenicline, and all nicotine replacement products; as a proxy for utilization of care, we extracted data on the number of post-period office visits per patient (≥6 vs. <6 visits) based on previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our primary outcome was tobacco cessation ("quit") during the post-period, coded as a binary yes/ no variable. Using methods similar to prior EHR-based studies, 11,[19][20][21][22] a person was identified as "quit" if the last recorded tobacco-use status during the pre-period indicated that the patient was a current user, and if there was at least one subsequent measurement documented in the postperiod that indicated the patient's status was a "nonuser" (eg, former user, not a current user). We extracted the following tobacco cessation medications from EHR medication orders: bupropion, varenicline, and all nicotine replacement products; as a proxy for utilization of care, we extracted data on the number of post-period office visits per patient (≥6 vs. <6 visits) based on previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Charlson Comorbidity Index (CCI) [4,5] was calculated from inpatient and outpatient ICD-10 diagnosis codes in the year before durvalumab start (Cohort 1) or the proxy durvalumab start date described below (Cohort 2). Smoking status was obtained through Health Factors data [6,7]. A concurrent chemotherapy regimen was obtained through intravenous infusion records and supplemented with the VACRS where available.…”
Section: Outcomes and Covariatesmentioning
confidence: 99%
“…Smoking cessation (‘quit’) at ≥1 visit during the post-period was coded as a binary yes/no variable. Using methods similar to prior EHR-based studies [ 31 35 ], a person was identified as ‘quit’ if there was at least one measurement documented in the post-period that indicated the patient’s status changed from one indicating current smoking to one indicating former smoking (regardless of whether the patient had a subsequent status that indicated a return to smoking). For smoking cessation medication provision, we extracted orders for bupropion, varenicline, and all nicotine replacement products from EHR medication orders.…”
Section: Methodsmentioning
confidence: 99%